FAKTOR-FAKTOR YANG MENYEBABKAN KECEMASAN IBU HAMIL TRIMESTER III DI PUSKESMAS WANASABA - Eka Mustika Yanti; Deby Kurnia Utami; Ariska Dwi Maulina (ProHealth Journal, 2020)
Objective: This research aims to examine in depth about the factors that cause the anxiety of the third trimester pregnant women in public health Wanasaba. Research Method:The study employed qualitative approach. The samples were taken though purposive sampling method. The technique of data collection was done through interview, observasi, audio visual, and study documentation. Research Result: The results of the interviews of the 5 subject of the study, found 12 factors that cause anxiety in the third trimester pregnant women (husband's Support, gymnastics pregnant, parity, age, health status, work, traumatic experiences, age of pregnancy, culture, live with parents/in-laws, level of education, pregnancy distance) Conclusion: Factors that can lower the anxiety level of the third trimester pregnant women is (the husband’s support, gymnastics pregnant, parity, age, health status, work, traumatic experiences, age of pregnancy, culture, live with parents/in-laws). While the factor that does not cause anxiety is (the level of education and pregnancy distance.